From Play to Learning : Designing a Transition Model to Early Childhood School Readiness - Hapidin Hapidin; Yuli Pujianti; Nurbiana Dhieni; Ade Dwi Utami (Aulad: Journal on Early Childhood, 2025)
This study aims to develop a contextual transition learning model to improve the readiness of early childhood schools in Jakarta. The method used is based on Borg & Gall's research and development process, which involves the stages of needs analysis, model design, limited testing, evaluation, and model refinement. A needs analysis of 150 children showed that 43% were ready, 38% were somewhat prepared, and 19% were not ready, with the main weaknesses identified in the social-emotional and independence aspects. The designed model consists of six phases: relaxation, orientation, exploration, collaborative planning, implementation, and expression, based on neuropedagogical principles. Limited testing results showed significant improvement, with the ready category increasing from 43% to 61%, while the not ready category decreased from 19% to 8%. Expert validation resulted in an average score of 3.78 (very good). These results suggest that the contextual transition model is effective in enhancing children's readiness and have implications for teacher practice, parental involvement, and systematic educational policy.